Comparative Efficacy of Organic Amendments and Chemicals in Managing Rice Root-Knot Nematode (Meloidogyne graminicola Golden and Birchfield) - Tiwari, Srijan; Manandhar, Hira Kaji; Pandey, Prem; Gupta, Manoj Kumar (Journal of the Plant Protection Society, 2024)
A screen house experiment was conducted during the rainy season, 2022, Department of Plant Pathology, Rampur, Chitwan to evaluate organic amendments and chemicals, viz. chicken manure, mustard cake, titepati (Artemisia vulgaris) leaves, asuro (Justicia adhatoda) leaves, neem (Azadirachta indica) leaves, fosthiazate 30% SL and emamectin benzoate 5% SG against rice rootknot nematode (Meloidogyne graminicola) in naturally infested soils. An individual pot size of 22 cm x 18 cm was used which was filled with 4 kg nematode-infested soil and rice seeds cv. Ekle were sown in pots at three spots. Similar to that, 5 days prior to planting, emamectin benzoate 5% SG was applied at 0.5 g/l of water and fosthiazate 30% SL was applied at 300 μl/l of water. In the case of botanicals, the leaves were chopped, air-dried and mixed with soil at the rate of 15 g/kg soil 10 days before sowing. Also, mustard cake and chicken manure at 10 g/kg soil were applied to the soil 5 days before sowing. All treatments significantly reduced both nematode population and gall numbers, and increased plant growth indices compared to untreated control. Fresh shoot weight, shoot length and root fresh weight were found significantly high in the pots treated with mustard cake @10 g/kg soil. However, root length was found highest in fosthiazate 30% SL at 90 days after sowing. Maximum reduction in gall numbers per plant, root-knot severity index and M. graminicola population in soil was recorded in pots treated with fosthiazate 30% SL followed by mustard cake @10 g/kg soil and neem leaves @15 g/kg soil.